2020
DOI: 10.1002/cncy.22295
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal cytology in oropharyngeal brushings and in oral rinses is not associated with HPV infection: The OHMAR study

Abstract: Background No screening is available for human papillomavirus (HPV)‐associated oropharyngeal cancers. The authors investigated whether cytology may be used as a screening tool and whether oral HPV infection is associated with cytologic abnormalities detected in oropharyngeal brushings and in oral rinse‐and‐gargle specimens from asymptomatic individuals at increased risk for oral HPV infection. Methods Specimens were collected from men who have sex with men at 6‐month intervals. Oropharyngeal samples and oral r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Oral cytology has also been investigated as a method to detect HPV-associated morphological changes in asymptomatic individuals. Different cytological techniques have been evaluated, although with low success [17][18][19][20]. A study based on oral liquid cytology with rinsing and shaving carried out with HIV-infected patients showed only 6% of the cytological alterations [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral cytology has also been investigated as a method to detect HPV-associated morphological changes in asymptomatic individuals. Different cytological techniques have been evaluated, although with low success [17][18][19][20]. A study based on oral liquid cytology with rinsing and shaving carried out with HIV-infected patients showed only 6% of the cytological alterations [19].…”
Section: Discussionmentioning
confidence: 99%
“…Different cytological techniques have been evaluated, although with low success [17][18][19][20]. A study based on oral liquid cytology with rinsing and shaving carried out with HIV-infected patients showed only 6% of the cytological alterations [19]. Another recent study in which conventional cytology was performed directly on the amygdala also observed 6% of atypia cases [20].…”
Section: Discussionmentioning
confidence: 99%
“…In the OHMAR study by Benevolo et al, testing of oropharyngeal cytobrush samples and oral rinse and gargle specimens were testing by cytological evaluation and HPV genotyping, respectively, in a group of men who have sex with men at 6-months intervals. The study found that infection of high-risk HPVs, including HPV 16 did not increase the risk for cytologic abnormalities [158]. While these and other studies highlight the growing value of oral cytology, further research is necessary to evaluate the efficacy of this screening methodology in the same light as HPV driven cervical cytology, including the inability to access the target anatomical sites region like the tonsils or base of the tongue [159].…”
Section: Screeningmentioning
confidence: 89%
“…The false-positive cases observed in our study showed “atypical” cells, most likely an overinterpretation of reparative changes as a consequence of the treatment received, representing a barrier when evaluating cytomorphology. Moreover, cytologic abnormalities in oropharyngeal brushings and oral rinses can be associated with smoking and drinking habits [ 22 , 26 ].…”
Section: Discussionmentioning
confidence: 99%